Falls-risk in senior women after radical treatment of breast cancer - Biskup, Małgorzata; Góźdź, Stanisław; Macek, Paweł; Opuchlik, Anna; Skowronek, Tomasz; Polit, Łukasz; Żak, Marek (Medical Studies/Studia Medyczne, 2017)
Introduction : It is estimated that 35–40% people over the age of 65 experience at least one fall per year; for those over the age of 80 this increases to 50%, and for residents of institutional care facilities, to 60%. Aim of the research : To evaluate the functional capacity and susceptibility to falling among women over 60 years of age, who had been treated for breast cancer. Material and methods : The study group comprised 173 women aged 61–85 years (mean: 68.75 years), all breast cancer survivors treated at the Holy Cross Cancer Centre in Kielce. Functional efficiency was measured using the Senior Fitness Test (SFT), and the falls-risk assessment was carried out using the POMA Tinetti test. An additional questionnaire was used to assess the anxiety associated with falls. The relationship between functional capacity and the falls-risk, and between the amount of medication used and the falls-risk, were also assessed. Results : In all SFT tests, the women had lower scores compared to the recommended standards. Medium and high falls-risk were reported in 27% of patients. Apart from an increase in falls-risk, the women reported poorer results in all physical fitness tests. An increase in the number of medications taken was associated with lower Tinetti test results. Conclusions: Women treated for breast cancer were exposed to a high falls-risk. The treatment management applied to women with breast cancer adversely affected their functional capacities. Furthermore, an increase in the amount of medication taken by post-mastectomy women resulted in a still higher exposure to falls-risk. Task-oriented, physical rehabilitation programmes should therefore promptly be introduced to address the problem of falls and resultant fractures among senior post-mastectomy women.